Effect of shrimp paste rice bran on fat deposition in broiler chickens: Pengaruh Terasi Dedak terhadap Deposisi Lemak pada Ayam Broiler - Pratama, Rohfiko Pajri; Santoso, Urip; Kaharuddin, Desia (Buletin Peternakan Tropis, 2024)
This study aims to evaluate the effect of providing shrimp paste rice bran on fat deposition in broilers. One hundred and sixty broilers (Lohmann strain) aged 15 days were distributed into 5 treatments with 4 replications namely control diet (P1), 5% shrimp paste rice bran (P2), 10% shrimp paste rice bran (P3), 15% shrimp paste rice bran (P4) and, 20% shrimp paste rice bran (P5). The results showed that the use of shrimp paste rice bran in the ration had a significant effect (P<0.05) on abdominal fat, ventricular fat (P<0.05), but had no significant effect (P>0.05) on proventriculus fat, heart fat, neck fat and sartorial fat. It can be concluded that giving 15-20% shrimp paste rice bran reduces abdominal and ventricular fat deposition in broiler chickens.